Modified detergent Ziehl-Neelsen technique for the staining of Cyclospora cayetanensis. Issue 6 (June 1996) - Clarke, S C; McIntyre, M
Abstract : Cyclospora cayetanensis is a cause of prolonged diarrhoea, mainly in travellers. Laboratory diagnosis may be achieved by a number of methods such as the staining of faecal smears by the modified Ziehl-Neelsen (ZN) technique. Safer methods using this technique have been described for the staining of acid fast bacilli and cryptosporidia by replacing the phenol content of the carbol fuschin stain with various concentrated detergents. In this report the technique was modified slightly using a non-concentrated detergent and applied to the staining of oocysts of C cayetanensis. It was found that oocysts of C cayetanensis do not stain using the modified detergent ZN method when compared with similar preparations containing oocysts of Cryptosporidium spp.